From Critical Existence to Critical Exception: Uses of Vulnerability in the Public Sphere in Chile; [de la Existencia Crítica a la Excepción Crítica: Usos de la Vulnerabilidad en la Esfera Pública en Chile] - Rojas-Lasch, C (Universidad Austral de Chile, 2025)
This article analyzes the discourse in the public field in Chile in the context of exception (socio-political and health crisis) from a critical approach to the study of vulnerability. We studied a sample of documents published in digital media between 2020 and 2022. We analyzed the development of a technical-political narrative that, although it allowed an opening up, unprecedented since the dictatorship, to more protectionist models of public policies, they were transitory and closed the horizons of a more structural transformation. We showed that what made this process possible was the building of critical existence and fear as emotional signs of political coexistence, highlighting and associating the family as a legitimate unit of recognizing vulnerability. Finally, we discussed the scope and effects of this political discourse on the development of a conservative wave in the current Chile. © 2025, Universidad Austral de Chile. All rights reserved.